0449 Leading and lagging indicators for the prevention of violence towards workers in health care. (21st August 2017) - McLeod, Christopher; Provost, Sharon; Choi, Kelvin; Amick, Benjamin; Astrakianakis, George
Abstract : Objectives: Violence towards health care workers is a pressing occupational health concern internationally. There are few frameworks and metrics developed to monitor and track the effectiveness of violence prevention activities. This study's aim was to develop leading and lagging indicators to be used in violence prevention activities in the health care sector in British Columbia, Canada. Methods: A systems framework identifying potential leading and lagging indicators was developed from a review of quantitative and quantitative research literature and from focus groups and key informant interviews with managers and frontline staff in two large health authorities. Evidence was synthesised using a realist review approach and priority indicators were developed in consultation with an employer/labour advisory panel. Data sources for potential indicators were identified and selected indicators were validated using incidence data on violence. Results: Indicators were identified across socio-political, organisational, environmental, patient and caregiver domains. The research literature tended to emphasise patient and caregiver factors, while manager and staff interviews emphasised organisational and environmental factors. Priority indicators were identified in areas of hazard identification and management, staffing and staff mix, communications, and education and training. Conclusions: Indicators for risk of violence need to be sensitive to context. While there is a considerable amount of data available for the development of leading and lagging indicators, challenges exist in coordinating data across multiple data stewards and little data is collected in some domains relevant to effective violence prevention. Future research will focus on validating indicators based on currently available data.